“Time without you”: Transition to widowhood and its impact on time perspective and attitudes toward the future - de Paula Couto, M. Clara; Kim-Knauß, Yaeji; Rothermund, Klaus; Fung, Helene H.; Hess, Thomas M.; Lang, Frieder (European Journal of Ageing, 2025)
Widowhood is a significant life event that can profoundly alter an individual’s perception of time. Those who have lost a spouse often find themselves reflecting on past memories, while simultaneously feeling disconnected from the present. However, the impact of widowhood on one’s experience and perception of time has not been thoroughly explored. In this study, we investigate changes in time perspective during the transition to widowhood using a multidimensional approach to temporal experience. This perspective enriches the existing literature, which has primarily focused on the predictive role of time perspective by providing new insights into how major life events can reshape an individual’s experience of time. The sample was drawn from seven measurement points between 2009 and 2023 in the Aging-as-Future longitudinal study. It consisted of 1357 participants aged 50 and older who either remained married throughout the study period (n = 1270) or transitioned to widowhood (n = 87). We assessed four facets of time perspective: past-orientation, feelings of obsolescence, concreteness of the future time, and attitudes toward life’s finitude as well as subjective life expectancy. While the transition to widowhood predicted an increase in past-orientation and in feelings of obsolescence, it predicted a decrease in concreteness of the future. Spousal loss did not influence individuals’ attitudes toward finitude, but those experiencing widowhood reported a decrease in their perceived remaining lifetime. Our study showed that widowhood may lead to shifts in time perspective. Findings underscore the value of considering time perspective as a key indicator of an individual’s adjustment and functioning in response to a major life event.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Critical life events; Fixed-effects panel regression models; Spousal loss; Subjective remaining life expectancy; Time perspective